The Relationship between Knowledge Management and Innovation Usage of Educational Personnel of Rajchanakarin School Consortium - Aiamsasithon, Nalinrat; Petchroj, Laddawan (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to study 1) knowledge management, 2) innovation usage, and 3) the relationship between knowledge management and innovation usage of educational personnel at Rajchanakarin School Consortium. The sample group consisted of 214 administrators and teachers, using a stratified random sampling according to school size. The instrument was a questionnaire with a content validity of 0.67-1.00 and a reliability of 0.70. The data were analyzed to find the mean, standard deviation, and Pearson's correlation coefficient. The research findings were as follows: 1) Overall and individual knowledge management was at a high level. The highest mean was knowledge indication, followed by the order of knowledge sharing, the pursuit of knowledge and knowledge creation of knowledge application, and knowledge storage. 2) The overall use of innovation was at a high level. The item with the highest average was set goals for using innovation clearly and jointly searching for ways to use innovations to develop the organization for efficiency. And 3) The relationship between knowledge management and innovation usage of educational personnel had a moderate relationship (r=.454**).